The supportive care needs of women experiencing gynaecological cancer: a Western Australian cross-sectional study - Williams, N.; Griffin, G.; Farrell, V.; Rea, A.; Murray, K.; Hauck, Yvonne (BioMed Central Ltd., 2018)
Background: Women diagnosed with gynaecological cancer experience supportive care needs that require care provision to reduce the impact on their lives. International evidence suggests supportive care needs of women with gynaecological cancer are not being met and provision of holistic care is a priority area for action. Knowledge on gynaecological cancer supportive care needs is limited, specifically comparison of needs and cancer gynaecological subtype. Our aim was to identify supportive care needs of Western Australian women experiencing gynaecological cancer, their satisfaction with help and explore associations between participant’s demographic characteristics and identified needs. Methods: A cross-sectional design incorporating a modified version of the Supportive Care Needs Survey - short form (SCNS-SF34) assessed 37 supportive care needs under five domains in conjunction with demographic data. Three hundred and forty three women with gynaecological cancer attending a tertiary public referral hospital completed the survey over 12 months. Statistical analysis was performed using the R environment for statistical computing. A linear regression model was fitted with factor scores for each domain and demographic characteristics as explanatory variables. Results: Three hundred and three women (83%) identified at least one moderate or high level supportive care need. The five highest ranked needs were, ‘being informed about your test results as soon as feasible’ (54.8%), ‘fears about cancer spreading’ (53.7%), ‘being treated like a person not just another case’ (51.9%), ‘being informed about cancer which is under control or diminishing (that is, remission)’ (50.7%), and ‘being adequately informed about the benefits and side-effects of treatments before you choose to have them’ (49.9%). Eight of the top ten needs were from the ‘health system and information’ domain. Associations between supportive care items and demographic variables revealed ‘cancer type’, and ‘time since completion of treatment’ had no impact on level of perceived need for any domain. Conclusions: Western Australian women with gynaecological cancer identified a high level of supportive care needs. The implementation of a supportive care screening tool is recommended to ensure needs are identified and care is patient-centred. Early identification and management of needs may help to reduce the burden on health system resources for managing ongoing needs.